The Influence of Student Engagement and Critical Thinking Abilities in Academic Writing - Tis’ah Mukarramah Khaerunnisa; Muhammad Tahir; Asriati Asriati (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
Student Engagement, Critical Thinking Abilities, Academic Writing. This study aimed to determine the effect of student engagement and critical thinking abilities in academic writing. The researcher uses the type of causal-comparative quantitative research. The research subjects were students who had taken Academic Writing courses in the 2024/2025 academic year, totaling 30 people. The subjects were selected using a research questionnaire and considering the students' final grades in the Academic Writing course. Research data were obtained by distributing research questionnaires and final grades in Academic Writing courses. The results show that both Student Engagement (p-value = 0.043) and Critical Thinking Abilities (p-value = 0.038) are significant at the 5% level, indicating a substantial impact on Academic Writing. The coefficients for Student Engagement (0.439) and Critical Thinking Abilities (0.400) suggest that increases in these variables lead to improvements in academic writing. Additionally, standardized beta values reveal that Critical Thinking Abilities (B = 0.387) have a slightly stronger influence than Student Engagement (B = 0.377). Overall, the findings demonstrate that enhancing both student engagement and critical thinking abilities contributes positively to academic writing performance.Keywo0rds: Students Engagement, Critical Thinking. Academic Writing